ChemInform Abstract: Palladium‐Catalyzed Amination of C‐5 Bromoimidazo[2, 1‐b][1, 3, 4]thiadiazoles. Issue 34 (4th August 2016) - Copin, Chloe; Buron, Frederic; Routier, Sylvain
Abstract: A library of C‐5 brominated substrates is prepared and subjected to amination under conditions A).